The Effect of Leadership Style and Work Control on Employee Performance at PT. Karya Semangat Mandiri - Sarris Pargaulan Nainggolan; Martua Sitorus (SEAN Institute, 2022)
This study aims (1) to determine the effect of Leadership Style on Employee Performance, (2) to determine the effect of Work Control on Employee Performance (3) to determine the effect of Leadership Style and Work Control on PT. Karya Semangat Mandiri. Based on the problem, this research is an ex post facto research and based on the level of explanation of the position of the variables of this research is a causal comparative research (causal-comparative research) with the unit of analysis studied are employees at PT. Karya Semangat Mandiri. This research is a population study with a population of 64 employees. The questionnaire was tested for validity and reliability before collecting research data. The test instrument used in this study used the classic assumption test which included the normality test, heteroscedasticity test and multicolonierity test. The data analysis method used is multiple regression analysis. The results of this study indicate that: (1) leadership style influences employee performance at PT Karya Semangat Mandiri, (2) work control affects employee performance at PT Karya Semangat Mandiri, (3) leadership style and work control simultaneously affects employee performance. at PT Karya Semangat Mandiri .